RNA-Binding Proteins in the Control of LPS-Induced Macrophage Response - Ostareck, Dirk H.; Ostareck-Lederer, Antje (Frontiers in Genetics, 2019)
Innate immune response is triggered by pathogen components, like lipopolysaccharides (LPS) of gram-negative bacteria. LPS initiates Toll-like receptor 4 (TLR4) signaling, which involves mitogen activated kinases and NFκB in different pathway branches and ultimately induces inflammatory cytokine and chemokine expression, macrophage migration and phagocytosis. Timely gene transcription and post-transcriptional control of gene expression confer the adequate synthesis of signaling molecules. As trans-acting factors RNA binding proteins (RBPs) contribute significantly to the surveillance of gene expression. RBPs are involved in the regulation of mRNA processing, localization, stability and translation. Thereby they enable rapid cellular responses to inflammatory mediators and facilitate a coordinated systemic immune response. Specific RBP binding to conserved sequence motifs in their target RNAs is mediated by RNA binding domains, like Zink-finger domains, RNA recognition motifs (RRM), and hnRNP K homology domains (KH), often arranged in modular arrays. Through the use of RNA immunoprecipitation and microarray analyses (RIP-Chip) and recently developed RNA protein crosslinking and RNA sequencing techniques (iCLIP, PAR iCLIP, RNA Seq) in macrophages, the functional analysis of specific RBPs and their global mRNA interaction profiles exhibited valuable information about inflammation related gene expression control. Mapping experiments employing LPS induction of macrophages as primary responding immune cells revealed a broad impact on intracellular signaling modulation, pathogen clearance and temporal cytokine expression, which regulates tissue- and organ specific immune activation. Here we focus on the RBPs TTP, HUR, TIAR and hnRNP K, and their impact on target mRNAs in the post-transcriptional control of LPS induced macrophage immune response.